2020
DOI: 10.1177/0162353220955230
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Serving English Learners in Gifted Education: Looking Back and Moving Forward

Abstract: Although the number of English learners (ELs) in the United States continues to increase, this population remains underserved by gifted and talented (GT) education programs across the nation. This underrepresentation represents a societal and research dilemma for reasons we address in this systematic review of the most effective practices documented to identify and serve ELs for GT programs. We examine 50 theoretical and empirical articles according to four major themes: nomination, screening/assessment, servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…The overarching study question focused on identification procedures and practices used in districts and schools successfully identifying ELs for gifted and talented programs. Based on literature reviews and our theory of change (Mun et al, 2016, 2020; Siegle et al, 2016), we identified four cross-cutting themes and professional experiences: patterns, processes, personnel, and problems. The initial grand tour questions for each participant group followed the same organizational structure:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overarching study question focused on identification procedures and practices used in districts and schools successfully identifying ELs for gifted and talented programs. Based on literature reviews and our theory of change (Mun et al, 2016, 2020; Siegle et al, 2016), we identified four cross-cutting themes and professional experiences: patterns, processes, personnel, and problems. The initial grand tour questions for each participant group followed the same organizational structure:…”
Section: Methodsmentioning
confidence: 99%
“…We created an EL codebook based on our theory of change (Mun et al, 2016; Siegle et al, 2016). The theory of change includes four phases related to the identification of ELs for gifted and talented programs: Pre-Identification, Preparation, Identification, and Acceptance of Placement.…”
Section: Methodsmentioning
confidence: 99%
“…Culturally relevant leadership in gifted education, from a systemic perspective, has great potential in transforming district policy and practices in ways that are inclusive of CLED students. Respective to CLED students and their lack of inclusion in GT programs, scholars have pointed to deficit views of students, their families, and the communities in which they live (Ford, 2014; Hernandez & Fraynd, 2014); inequitable identification of policies and practices (Mun, 2016; Mun et al, 2016; Siegle et al, 2016); and differential access to resources (Hamilton et al, 2018; Siegle et al, 2014). We recognize the greater body of literature, in gifted education (e.g., Davis et al, 2013; Renzulli, 2012; Subotnik et al, 2014) and culturally relevant leadership (e.g., Beachum, 2011; Horsford et al, 2011; Johnson & Fuller, 2014; Khalifa et al, 2016), and consider this systematic literature review as a means to narrow the gap at the intersection of the two and complementary to the greater body of scholarship.…”
Section: Discussionmentioning
confidence: 99%
“…Culturally, linguistically, and economically diverse (CLED) student populations in the United States have grown exponentially in the last half century, but gifted and talented (GT) programs have failed to reflect this diversity. Researchers have consistently pointed to inequitable identification of policies and practices, teacher deficit views, and differential access to resources to explain the dearth of CLED learners in gifted programs across the nation (Baldwin, 2002; Ford, 2014; Graham, 2013; Hamilton et al, 2018; Mun et al, 2016; Siegle et al, 20l4). Challenges with funding gifted programs due, in part, to a lack of a federal mandate also have been problematic for serving GT students (Jolly & Robins, 2016).…”
mentioning
confidence: 99%
“…A lack of such cohesion has been connected to the long-standing disparities in advanced academic representation and educational performance of CLED students (Goings & Ford, 2018; Peters et al, 2014; Plucker & Peters, 2016). Cultural deficit views, racism, differential access to resources, biased standardized assessments, use of rigid cutoff scores, and a lack of culturally relevant professional development have been noted as potential contributors to low representation of CLED populations in gifted programs (Ezzani & Brooks, 2019; Ford, 2014; Lockhart & Mun, 2020; Mun, 2016; Mun, Hemmler, et al, 2020; Siegle et al, 2016; Valencia, 2012). System leaders are urged to implement culturally relevant policies and practices to build systemic capacity and produce equitable reform (Horsford et al, 2011).…”
Section: Leadership For Systemic Change In Gifted and Talented (Gt) Ementioning
confidence: 99%